Tingkat Adopsi Pengelolaan Tanaman Terpadu (PTT) di Kecamatan Insana Utara - Suri, adenala odilia suri; Joka, Umbu; tabenu, Oktovianus (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2025)
The use of agricultural technology in rice cultivation in North Insana Kecamatan is still very rudimentary. To increase rice productivity, farmers have attempted to develop integrated crop management (ICM) techniques, a series of techniques that can be adapted to local climatic conditions. This study involved 95 respondents from rice farmers in North Insana District. Data analysis used a struges analysis tool. The results showed that the average quality of integrated crop management (ICM) components among farmerJurnal Agrifos reached 43%. This value is considered low, indicating that few farmers have adopted the quality of integrated crop management (ICM) components, such as the use of easy-to-seed seedlings, the number of seedlings per hole, and harvesting according to the age of New Superior Varieties (VUB).